Identidades porosas, estructuras sincréticas y narrativas dominantes: miradas cruzadas entre Pierre Sanchis y la Argentina = Porous identities, syncretic structures, and dominant narratives : crossed glances between Pierre Sanchis and Argentina - Frigerio, Alejandro (Ciencias sociales y religión, 2005)
The article critically reviews some of the contributions that Pierre Sanchishas made to the study of the Brazilian religious field, emphasizing his ideas onsyncretism, on the permeable character of religious identities and on Catholicismas a habitus. The first part of the paper uses some of the insights developed bySanchis to reassess Argentine studies on religion. In the second part, Sanchis’work is itself examined through the lenses of an Argentine anthropologist. Finally,the paper discusses how the different dominant narratives of the nation present ineach country condition local studies on religion.